Rediseño del proceso de cosecha y empaque de banano para exportación implementando software de modelado y análisis de simulación 3d, en las haciendas Agrilecho 1, Agrilecho 2 y Libertad de la empresa Reybanpac ubicadas en el cantón Valencia - Aurea Maquilon, Jerry Felix (2022)
This research project is based on the "Redesign of the process of harvesting and packing bananas for export by implementing modeling software and 3D simulation analysis, in the Agrilecho 1, Agrilecho 2 and Libertad farms of the Reybanpac company located in the Valencia canton. .”, having as a first analysis the current situation of the work method, thus managing to examine the way in which the activities are carried out in order to simplify or modify them and therefore reduce the unnecessary or excessive work that is causing delays in production due to losses. of times or dead times and from there to obtain the standard time of the activities that the workers of the packing process intervene for the production of banana boxes. The farms of the Reybanpac company have a continuous process production line and these are manual operations, so a study of the OEE calculation, availability of time, performance of work speed and the quality of the products was carried out to indicate the performance and productivity, then carrying out a new distribution for an improvement in the restructuring of jobs and thus increase productivity. And through the virtual simulation of the current and proposed production line, it allowed us to virtually carry out what would happen in reality, thus verifying the increase in the productivity of banana boxes. Keywords: process, OEE calculation, distribution, simulation.